상호작용적 디지털 가드닝을 이용한 가상과 물리 공간 통합 연구: 그림자 꽃 프로젝트 - 장운정(Woon-Jung Jang ); 권두영(Doo-Young Kwon) (디지털콘텐츠학회논문지, 2023)
본 연구는 "그림자 꽃(Shadow Flower)" 프로젝트를 중심으로, 관람객의 참여를 통한 실시간 인터랙티브 체험의 가능성을 탐구한다. 관람객은 자신의 신체 움직임을 이용하여 가상의 꽃을 디자인하고 발전시키며, 이 과정에서 신체 움직임 데이터는 실시간으로 수집된다. 수집된 데이터는 가상의 꽃과 사운드를 동적으로 변화시키는 데 사용된다. 본 연구는 가상 공간, 물리적 공간, 그리고디지털 미디어가 어떻게 유기적으로 통합될 수 있는지를 탐구하고, 체험형 전시 콘텐츠의 가능성을 확장하려고 한다. "그림자 꽃"프로젝트는 '드로잉 가든(Drawing Garden)', '그림자 화분(Shadow Pot)', 그리고 '그림자 사운드(Shadow Sound)' 세 가지 주요 공간모듈로 구성된다. 각 모듈은 독특한 인터랙션 체험을 제공한다. 키넥트(Kinect) 센서와 사운드 생성 알고리즘을 활용하여 관람객의 움직임을 음악적 표현으로 변환한다. 전시가 종료된 후에도 관람객은 실제 씨앗을 제공받아, 이를 실생활의 가드닝 체험과 연결시킬 수 있다. 이것은 전시의 일회성을 극복하고, 체험 가치를 오랫동안 유지하고 보다 풍부하게 만드는 것을 목표로 한다. The potential for real-time interactive experiences is explored through audience participation, with a focus on the "ShadowFlower" project. Visitors can use their body movements to design and grow virtual flowers, and the movement data are collectedin real time. The collected data are used to alter virtual flowers and sound dynamically. This research aims to investigate waysto integrate the virtual space, physical space, and digital media organically and seeks to expand the possibilities of experientialexhibition content. The "Shadow Flower" project includes three main spatial modules: "Drawing Garden," "Shadow Pot," and"Shadow Sound," each offering unique interactive experiences. The project employs Kinect sensors and sound generationalgorithms to convert visitor movements into musical expressions. After the exhibition has concluded, visitors receive real seeds,allowing them to connect their experience with real-life gardening. The objective is to overcome the temporality of the exhibitionand to sustain and enrich the experiential value over time. KCI Citation Count: 0